Occupation as marker of self: Occupation in relation to self among people with advanced cancer. (2nd January 2019) - Maersk, Jesper Larsen; Johannessen, Helle; la Cour, Karen
Abstract: Background: Living with advanced cancer can have a profound impact on the person's self . A person's self is influenced by various aspects of daily life, including engagement in occupation. From an occupational perspective, little research has been done to explore how the self of people with advanced cancer is formed through their engagement in occupation. Aim: The purpose of this study was to explore how people with advanced cancer experience that their sense of self is formed through engagement in occupation. Methods: A total of 28 interviews were conducted with 22 people with advanced cancer. Grounded theory guided the collection and analysis of data. Results: 'Occupation as marker of self' was identified as the core category. Occupations served as markers of the participants' self (1) by mirroring their abilities and positioning of their self in the illness trajectory; and (2) as means of expressing their self. The core category provided explanations about how the participants' experiences of occupation influenced their self-perceptions, as explained in the sub-categories 'defining the self through occupation' and 'reassessing self and accepting limitations'. Conclusions: For people with advanced cancer, engagement in occupation influences their self as current abilities become apparent and positions of their self can be created and expressed.